Maritime hominin dispersals in the Pleistocene: advancing the debate. (4th April 2017) - Leppard, Thomas P.; Runnels, Curtis
Abstract : To what extent is there spatial and temporal patterning in the spread of our genus around the planet, and what environmental and behavioural factors specify this patterning? The prevailing model of Pleistocene dispersals of Homo holds that this process was essentially terrestrial, with oceans and seas inhibiting and directing the movement of hominins out of Africa (e.g. Mellars2006 ; Dennell & Petraglia2012 ; Gamble2013 ), although some scholars propose short-range maritime hops at both the Strait of Gibraltar and Bab-el-Mandeb (Lambeck et al. 2011 ; Rolland2013 ). The relatively recent discovery of stone tools with apparently Lower and Middle Palaeolithic characteristics on islands in the eastern Mediterranean and in Island Southeast Asia (ISEA) has, however, been used by some scholars to challenge this terrestrial model.